Central Odontogenic Fibroma with the Presence of Large Fibroblasts of Varying Morphology - Costa, Victor [UNESP]; Anbinder, Ana Lia [UNESP]; Herrera, Fernanda [UNESP]; Rodrigues, Nayara [UNESP]; Cavalcante, Ana Sueli Rodrigues [UNESP]; Kaminagakura, Estela [UNESP] (Springer Nature, 2020)
A patient with an odontogenic fibroma (OF) with the presence of fibroblasts of varying morphology is presented, and the main microscopic differential diagnosis is discussed. Case report: a 51-year-old man complained of a swelling in the anterior region of the mandible. The panoramic radiograph showed a radiolucent, well-defined multilocular image, with displacement of the roots of the left mandibular incisors and canine. A cone beam computed tomography examination revealed a hypodense image, with delicate bone spicules inside, divergence of the tooth roots and destruction of the buccal cortical bone. Under the differential diagnosis of a desmoplastic ameloblastoma or a squamous odontogenic tumor, an incisional biopsy was made. Microscopically, deeply collagenized tissue with scarce odontogenic epithelium islands, large fibroblasts of varying morphology and calcified material was observed. A diagnosis of OF was made. Surgical removal was carried out, and the specimen was examined. Identical aspects were found, and the immunohistochemical reaction for pan-cytokeratin was carried out to identify the odontogenic epithelial cells. The definitive diagnosis of OF was confirmed, and we emphasize the importance of the correlation of all characteristics for a definitive diagnosis.
Keywords: Desmoplasia; Large fibroblast; Odontogenic tumor